The barley (hordeum vulgare): special plant described in the Quran - Mohd Arif Nazri,; Nurul Jannah Zainan Nazri,; Nurul Mukminah Zainan Nazri, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The present work is an analysis of nine Quranic verses and their interpretations which specifically described barley (Hordeum vulgare). The main objective of this study is to establish how Allah described different parts of barley and how the verses are interpreted as well as identifying the various benefits of barley as a wholesome food. To achieve this, comprehensive and detailed data was systematically collected from the Quran, books of commentary as well as references which contain scientific findings related to barley. The study found that Allah SWT uses merely inclusive terms like habb, habba, habbah which indirectly denote grains. Therefore, interpreters of the Quran along with translators form diverse yet all-encompassing interpretations and translations of the inclusive terms. Based on the analysis, the nine Quranic verses were found to define barley as a plant that is harvested with its roots. It is also regarded as a nutritious food for humans and cattle. Its stalks contain grains, they grow when watered and it has no nuclei. Its size is small, and the grains are clustered together.